The effect of Knowledge Management, Entrepreneurial Orientation, Transformational Leadership, and Management Control System on Learning Organization - Jauhara; Ramaditya, Muhammad (Research of Islamic Economics, 2023)
This study investigates the strategy for developing an organizational learning culture at PT Bank Syariah Indonesia Branch Office Jakarta Bendungan Hilir. It employs four independent variables, namely knowledge management, entrepreneurial orientation, transformational leadership, and control management systems, with organizational learning as the dependent variable. The survey method is used, and data is collected through a questionnaire administered to all employees, with a sample of 71 respondents analyzed using SPSS 25. The findings indicate that knowledge management, entrepreneurial orientation, transformational leadership, and control management systems do not directly impact organizational learning. However, when considered collectively, these factors significantly influence the formation of an organization's learning culture, accounting for 71.9% of the variance. This study examines the collective impact of knowledge management, entrepreneurial orientation, transformational leadership, and control management systems on developing an organizational learning culture. The findings provide organizations with valuable insights to make informed decisions that enhance learning capabilities and cultivate a culture prioritizing continuous learning and improvement. Recognizing the significance of these factors enables organizations to shape their practices and policies, fostering a strong learning environment, facilitating knowledge sharing, and driving innovation.